2016
DOI: 10.1039/c5ta10552h
|View full text |Cite
|
Sign up to set email alerts
|

Silica-templated ordered mesoporous carbon thin films as electrodes for micro-capacitors

Abstract: High performance electrodes for micro-capacitors were synthesized by tuning thickness and porosity of mesoporous carbon and composite silica/carbon thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 69 publications
(96 reference statements)
3
18
0
Order By: Relevance
“…As in PAS method, the ratio of 2ϒ photon reflects the collision frequency with pore walls, which affects the Ps lifetime, therefore, the porosity properties can be derived . Tang et al have used PALS method to explore the pore interconnectivity of porous silica thin film, a frequently used template for porous carbon electrodes . The Ps 3γ‐annihilation fraction was highly related to the diffusion of Ps, the diffusion of which was governed by the interconnectivity of the porous silica thin‐film.…”
Section: Design Considerations and Performance Metrics For Microsupermentioning
confidence: 99%
“…As in PAS method, the ratio of 2ϒ photon reflects the collision frequency with pore walls, which affects the Ps lifetime, therefore, the porosity properties can be derived . Tang et al have used PALS method to explore the pore interconnectivity of porous silica thin film, a frequently used template for porous carbon electrodes . The Ps 3γ‐annihilation fraction was highly related to the diffusion of Ps, the diffusion of which was governed by the interconnectivity of the porous silica thin‐film.…”
Section: Design Considerations and Performance Metrics For Microsupermentioning
confidence: 99%
“…While nanocasting is very versatile in terms of approachable pore structures and material morphologies, thin‐film engineering of hard‐templated OMCs is rather challenging. As one example, Levi‐García et al reported the synthesis of an ordered mesoporous silica thin film with mesopores of around 8 nm in size perpendicularly disposed to a graphite substrate followed by nanocasting transformation to an OMC thin film with mesopore sizes in the range of 2–3 nm ( Figure A) . Applications of hard‐templated carbon thin films are mainly located in the fields of electrochemical energy storage, electrocatalysis (e.g., in fuel cells) , or in gas sensing .…”
Section: Controlled Synthesis Of Nanoporous Carbon Thin Films and Appmentioning
confidence: 99%
“…As one example, Levi‐García et al reported the synthesis of an ordered mesoporous silica thin film with mesopores of around 8 nm in size perpendicularly disposed to a graphite substrate followed by nanocasting transformation to an OMC thin film with mesopore sizes in the range of 2–3 nm ( Figure A) . Applications of hard‐templated carbon thin films are mainly located in the fields of electrochemical energy storage, electrocatalysis (e.g., in fuel cells) , or in gas sensing . Nevertheless, synthesis of binder‐free carbon thin films with well‐ordered mesopores and high mechanical stability remains complicated with the nanocasting approach.…”
Section: Controlled Synthesis Of Nanoporous Carbon Thin Films and Appmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of mesoporous silica in 1990s, [13] ad iverse range of porous powders and films has been produced through hard-(e.g.,o rdered mesoporous silica, latex polymer beads) [14][15][16][17] and soft-templating (e.g.,s urfactants, triblock copolymers) [18][19][20][21][22][23][24][25] approaches. The templates can be removed by decomposition (calcination) with as tructuralt ension.…”
Section: Introductionmentioning
confidence: 99%